Image-Guided Robotic Radiosurgery for the Management of Spinal Ependymomas - Ehret, Felix; Kufeld, Markus; Fürweger, Christoph; Haidenberger, Alfred; Windisch, Paul; Senger, Carolin; Kord, Melina; Träger, Malte; Kaul, David; Schichor, Christian; Tonn, Jörg-Christian; Muacevic, Alexander (Frontiers in Oncology, 2021)
Background Ependymomas are rare neoplasms of the central nervous system (CNS), usually localized intracranially and most commonly diagnosed in children. Spinal ependymomas are more frequent in young adults and may be either primary lesions or manifest as disseminated seeding of cranial tumors. Data on the management of spinal ependymoma lesions remain scarce, especially concerning stereotactic radiosurgery (SRS) and stereotactic body radiation therapy (SBRT). The purpose of this study is to report the treatment outcomes of two institutions using robotic radiosurgery (RRS) for the treatment of spinal ependymomas. Materials and Methods All patients with a histopathologically confirmed diagnosis of an ependymoma WHO grade II or III who were treated with RRS for one or more spinal lesions were included in this analysis. Primary and adjuvant treatments were eligible for analysis. Results Twelve patients underwent RRS for the treatment of 32 spinal ependymoma lesions between 2005 and 2020. Two patients were below the age of 18 when treated, whereas nine patients (75%) suffered from a primary spinal ependymoma. The median dose was 15 Gy prescribed to a median isodose of 70%, with 27 lesions (84%) receiving a single-session treatment. The local control (LC) after a median follow-up of 56.7 months was 84%. LC rates at 1, 3 and 5 years were 92, 85 and 77%, respectively. The Kaplan-Meier estimated overall survival after 1, 3 and 5 years were 75, 75, and 45%, respectively. Five patients died, all of them suffering from an anaplastic ependymoma, with widespread CNS tumor progression being the reason for death in four patients. The majority of patients (58%) showed a stable neurological status at the last available follow-up. Overall, the treatment was well tolerated. Conclusion RRS appears to be a safe and efficient treatment modality for managing primary and secondary spinal ependymal tumors in patients with multiple lesions and local recurrences after surgical resection and adjuvant radiotherapy.